2017
DOI: 10.1108/srj-04-2015-0048
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mediating role of intellectual capital and competitive advantage on the relation between CSR and financial performance in SMEs

Abstract: Purpose The relationship between corporate social responsibility (CSR) and financial performance (FP) is a much-researched topic in academic arena. Recent studies disclosed that intellectual capital (IC) significantly impacts the success and survival of organizations. Moreover, theoretical assertions confirm that competitive advantage (CA) mediates the association between IC and FP. This has opened up new dimensions for the study. Therefore, this study aims to develop a theoretical model, first, to specify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
107
1
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(130 citation statements)
references
References 76 publications
13
107
1
9
Order By: Relevance
“…For instance, Jain et al (2017) and Nardo and Veltri (2014) scrutinized that CA fully mediates the relationship between IC and a firm's performance. Hence the same results are found in the present study and confirmed H6 of the study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Jain et al (2017) and Nardo and Veltri (2014) scrutinized that CA fully mediates the relationship between IC and a firm's performance. Hence the same results are found in the present study and confirmed H6 of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is contended that IC does not directly impact performance, but firm's internal strategic posture and CA mediate the relationship (Kianto, Andreeva, & Pavlov, 2013;Talebi, Rezazadeh, & Najmabadi, 2015). In the same nature, some studies have argued that IC is a set of intangible assets and resources to help firms to build CA which in turn provides the benefit of higher performance and profitability (Berzkalne & Zelgalve, 2014;Jain et al, 2017). Thus, we propose a hypothesis as:…”
Section: Competitive Advantage As a Mediator Between Intellectual Capmentioning
confidence: 95%
See 1 more Smart Citation
“…Prior studies documented the significant contribution of CSR (Javed et al, ; Rivera, Muñoz, & Moneva, ), IC and FC (Čater & Čater, ; Ling, ; Monteiro et al, ) to SCA and FP (Branco & Rodrigues, ; Fonseka et al, ; Surroca et al, ). Nonetheless, the role of the aforementioned factors is debated extensively in large firms mainly in developed and Western countries (Ayuso & Navarrete‐Báez, ; Jain, Vyas, & Roy, ; Kim, Kim, & Qian, ), but SMEs in the emerging economies seldom are articulated despite their dominant role in these markets (Bai & Chang, ; Khalique, Bontis, Abdul Nassir bin Shaari, & Hassan Md. Isa, ; Lee, Kwak, & Park, ).…”
Section: Introductionmentioning
confidence: 99%
“…Iraldo, Testa, Lanzini, & Battaglia, 2017) and the benefits of environmental policies on financial performance(Bagur-Femenias, Perramon, & Amat, 2015) in the other. Some articles employ empirical analysis to the emerging economies by observing interrelationships among resources, capabilities, and financial performance, also referring to the issues and theoretical approaches mentioned above(Jain, Vyas, & Roy, 2017) Sok, O'Cass, and Miles (2016),. for example, situate the analysis on the resource-based view, considering product innovation and marketing as resources and capabilities.…”
mentioning
confidence: 99%